Multi-Stage Fitness Test Performance, V˙O2 Peak and Adiposity: Effect on Risk Factors for Cardio-Metabolic Disease in Adolescents - Dring, Karah J.; Cooper, Simon B.; Morris, John G.; Sunderland, Caroline; Foulds, Gemma A.; Pockley, Alan Graham; Nevill, Mary E. (Frontiers in Physiology, 2019)
The role of physical activity in determining the metabolic health of adolescents is poorly understood, particularly concerning the effect on low-grade chronic inflammation (chronic elevation of pro-inflammatory cytokines IL-1β, IL-6, TNF-α and acute phase protein CRP, which is implicated in the etiology of atherosclerosis) and anti-inflammatory mediators such as IL-10. Furthermore, there is limited information on the mediating effects of performance on the multi-stage fitness test (MSFT), V˙O2 peak and adiposity on risk factors for cardio-metabolic disease in adolescents. Purpose: To examine the effect of performance on the MSFT, V˙O2 peak and adiposity on risk factors for cardio-metabolic diseases in adolescents. Methods: Following ethical approval, 121 adolescents (11.3 ± 0.8 year) completed the study. Risk factors for cardio-metabolic disease (circulating inflammatory cytokines, blood glucose and plasma insulin concentrations) was assessed using a fasted capillary blood sample. Participants were separated into quartiles based upon distance ran during the MSFT, the blood lactate response to submaximal exercise, V˙O2 peak (determined during an uphill graded treadmill test), and adiposity (determined as the sum of four skinfolds). The blood lactate response to submaximal exercise and V02 peak were measured in a sub-group of participants. Data were analyzed using two-way between-subjects ANCOVA and multiple linear regression. Results: Participants with the lowest performance on the MSFT had higher blood concentrations of IL-6 (3.25 ± 0.25 pg mL-1) and IL-1β (4.78 ± 0.54 pg mL-1) and lower concentrations of IL-10 (1.80 ± 0.27 pg mL-1) when compared with all other quartiles (all p < 0.05). Yet, when categorized into V˙O2 peak quartiles, no differences existed in any of the inflammatory mediators (all p > 0.05). Performance on the MSFT was the only predictor of IL-6 (β = -0.291, p = 0.031), IL-1β (β = -0.405, p = 0.005), IL-10 (β = 0.325, p = 0.021) and fasted blood glucose (β = -0.545, p < 0.001) concentrations. Adiposity was the only predictor of plasma insulin concentration (β = 0.515, p < 0.001) and blood pressure (diastolic: β = 0.259, p = 0.042; mean arterial pressure: β = 0.322, p = 0.011). Conclusion: Enhanced performance on the MSFT, but not V˙O2 peak, was associated with a favorable inflammatory profile in adolescents; whilst adiposity adversely affected plasma insulin, diastolic and mean arterial blood pressure. These findings demonstrate that enhancing performance on the MSFT and maintaining a healthy body composition are a potential therapeutic intervention for the attenuation of risk factors for cardio-metabolic diseases in adolescents.